Evaluation of Anti-Ulcer Activity of Ethanolic Extract of Leaves of Calophyllum Inophyllum (Calophyllaceae) in Rats - J. Banu Rekha (Journal of Global Pharma Technology, 2019)
Calophyllum inophyllum (CI) (Linn.) has been used to treat gastric ulcer in Indian folk medicine, but its efficacy has not been validated. The present study was carried out to evaluate the anti-ulcer activity of 80% ethanol leaf extract of Calophyllum inophyllum in rats. The effect of its extract on gastric ulcer in rats in pylorus ligation-induced and ethanol-induced models were studied using single dosing (200,400 mg/kg) and repeated dosing (200 mg/kg for 10 and 20 days) approaches. Ranitidine (50 mg/kg) and Sucralfate (100 mg/kg) were used as the standard drugs. Depending on the model, outcome measures were volume and pH of gastric fluid, total acidity, ulcer score, percent inhibition of ulcer score, ulcer index as well as percent inhibition of ulcer index. The extract possesses both dose-dependent and time-dependent anti-ulcer effect in the two models. The oral median lethal dose (LD50) is estimated to be higher than 2000 mg/kg for the alcoholic extract and secondary metabolites such as flavonoids, terpenoids, tannins and saponins were present. The findings of this study confirmed that the extract has anti-ulcer pharmacologic activity due to one or more of the secondary metabolites present in it. Therefore, this study validates its anti-ulcer use in Indian folk medicine. Further investigations on isolation of specific phytoconstituents and elucidating mechanisms of action are needed.Keywords: Antiulcer activity, Calophyllum inophyllun, Ranitidine, in vivo, Ethanolic Extract.